2022
DOI: 10.1051/e3sconf/202233405002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of a PEM fuel cell for marine power generation

Abstract: This study is focused on the possible application of hydrogen-fed PEM fuel cells on board ships. For this purpose, a test plant including a 100 kW generator suitable for marine application and a power converter including a supercapacitor-based energy storage system has been designed, built and experimentally characterised. The plant design integrates standard industrial components suitable for marine applications that include the technologies with the highest degree of maturity currently available on the marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Depending on the specific system and the type of power converter used, it is generally characterized by an efficiency exceeding 97% [22]. An examination of a 100 kW generator system incorporating ultracapacitors for energy storage demonstrated that at a load of 45 kW, the efficiency of DC/AC power conversion using a prototype converter reached 96.2%, and for an 80 kW load, it was 94.9% [23]. In a system equipped with a 5 kW cell, operating within a load range of 0.3 kW to 1.6 kW, the efficiency of the DC/DC converter ranged from 97% to 98% [24].…”
Section: Current Research Status Of Pem Fuel Cellsmentioning
confidence: 99%
“…Depending on the specific system and the type of power converter used, it is generally characterized by an efficiency exceeding 97% [22]. An examination of a 100 kW generator system incorporating ultracapacitors for energy storage demonstrated that at a load of 45 kW, the efficiency of DC/AC power conversion using a prototype converter reached 96.2%, and for an 80 kW load, it was 94.9% [23]. In a system equipped with a 5 kW cell, operating within a load range of 0.3 kW to 1.6 kW, the efficiency of the DC/DC converter ranged from 97% to 98% [24].…”
Section: Current Research Status Of Pem Fuel Cellsmentioning
confidence: 99%
“…There are mainly four ways for cooling PEMFC systems: edge cooling, air cooling, liquid cooling, and phase-change cooling [119]. Liquid cooling is often preferable due to its large cooling capability and good efficiency, and demineralized water or mixtures of demineralized water and ethylene glycol are usually implemented as refrigerants [120]. The main components of a liquid cooling system are the following: a circulating pump to guarantee a sufficient flow of refrigerant in the stack; a refrigerant reservoir; a heat exchanger to dissipate the heat either to the environment or to a heat recovery system; and a deionizer, which should be encompassed to guarantee that the refrigerant conductivity remains under set levels to avoid the short circuit of the PEMFC stack.…”
Section: The Main Power Source: Pemfcmentioning
confidence: 99%
“…For simplicity, not all components of the power conditioning, control, and monitoring subsystem of the BoP have been reported in the schematic. Elaborated from[120].…”
mentioning
confidence: 99%
“…Air compressor also tends to consume the highest auxiliary load among the BoP components [27]. Boosting too much air into the cathode may increase power output, but costs even higher BoP parasitic losses, lowering FCS efficiency [173,174]. Maintaining the right cathode partial pressure and stoichiometric intake air ratio during high load-high mass flow operation can be a challenge from design/control limitations of the air system leading to a compromise on FC efficiency and cathode side starvation [61].…”
Section: Air Systemmentioning
confidence: 99%